Tutur Kata Penonton Piala Dunia 2022 - Andi Saadillah; Saputra M, Muhammad Randi; Satria, Yunan Mahastra (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
2022 World Cup international event. Furthermore, the context of the audience's speech while watching together provides an overview of how Indonesian people express themselves through speech when watching World Cup matches. The purpose of this study is to explore the forms of speech acts by the public during collective World Cup viewing. The research was conducted in the city of Kolaka, Southeast Sulawesi, using qualitative research methods. Data collection techniques included observation, recording, note-taking, and interviews. Based on the described research results, the identified forms of speech acts tend to be expressive and emotional. Declarative speech acts accounted for 6 instances, imperative speech acts for 4 instances, and interrogative speech acts for 4 instances. The audience's speech patterns were influenced by factors such as the atmosphere, gender, and age. The study findings illustrate the dynamic nature of the audience's response, as the unpredictable World Cup matches often exceeded the audience's expectations. Consequently, people's words when watching the 2022 World Cup together could change depending on the ongoing match situation and conditions. Emotions such as joy, disappointment, sadness, annoyance, and disbelief were common expressions witnessed during these matches.